CENTRAL FIGURES OF SPORTS MARKET IN TURKEY: THREE BIGGEST AND THEIR MARKETING OPERATIONS - Hakan KATIRCI (Pamukkale University, 2011)
Nowadays professional sports have emerged as an industry and football industry is an important part of sport industry. A quick glance at football in Turkey will reveal that the football industry has developed rapidly after 1980's. Turkish football revenues have reached 342 million € in 2008-2009 football season and took place in the top ten in European football revenues. Istanbul clubs (Beşiktaş GK, Fenerbahçe SC, and Galatasaray SC), as called Three Biggest, have received a significant portion of these revenues. The basic aim of this paper is to examine Turkish football market, especially Beşiktaş Gymnastic Club, Fenerbahçe Sport Club, and Galatasaray Sport Club's (as called Three Biggest) market share and their marketing operations.